Experimental study on strength reduction due to corrosion in reinforced concrete slabs with and without steel fibers - Hnin Hnin Kyu; Khin Su Su Htwe (Innovation in Engineering, 2025)
Corrosion significantly affects deterioration in reinforced concrete structural members, severely compromising their strength and durability, especially in regions with heavy rainfall and exposure in coastal areas. Currently, steel fibers have been increasingly used in the construction industry because of their enhanced durability, crack resistance and overall structural performance and it’s been emphasized for more research. Moreover, most previous studies have focused on corrosion damage in reinforced concrete slabs and beams, further research is needed to study the behavior of corrosion in RC slabs with steel fibers and the proneness of steel fibers to corrosion. This study aims to experimentally evaluate the impact of corrosion on the flexural strength and durability of steel fiber-reinforced concrete (SFRC) slabs comparing with conventional reinforced concrete (RC) slabs. An accelerated corrosion process was applied using a 5% sodium chloride electrolyte solution and a 5V output over 240 days. Corrosion levels in the slabs were assessed by using the Cor-Map technique. The results indicated that SFRC slabs exhibited higher corrosion levels than conventional RC slabs, likely due to the increased exposed area from the distributed steel fibers. The results of experimental flexural strength tests showed that the percentage reduction in flexural strength of the SFRC slab was greater than that of the conventional RC slab after corrosion. Although SFRC slabs exhibited faster corrosion due to the presence of steel fibers, fiber corrosion did not contribute to the corrosion of main steel bars and these slabs performed better than conventional RC slabs in terms of flexural strength and crack resistance in both before and after corrosion. According to this experimental research, the behavior of steel fiber corrosion in RC slabs is well known, and it showed that steel fibers could be effectively used in RC slabs and these results provided a valuable reference for assessing the residual capacities of existing steel fibers reinforced concrete slabs affected by corrosion.